FINANCIAL TECHNOLOGY AND SHARIA COMPLIANCE REGULATIONS IN ISLAMIC BANKING IN INDONESIA - Dwi Swasana Ramadhan (Universitas Islam Negeri (UIN) Walisongo Semarang, 2022)
Purpose: The purpose of this study is to analyze the FinTech phenomenon and compliance with sharia regulations in Islamic banking in Indonesia. Use of research as information for regulators, Islamic banking, and other stakeholders in compiling compliance regulations as an element of supervision and optimal strategy to improve the quality of FinTech in Indonesian Islamic banking.Method: This research is a qualitative case study with literature studies related to the phenomenon of Sharia FinTech and Islamic regulations in Islamic banking in Indonesia.Results: The results of Yudaruddin's research (2022) stated that the better the economic conditions, the higher the potential for FinTech growth. Meanwhile, the results of Muryanto's research (2022) stated that apart from focusing on FinTech, Islamic banking is also required to maintain compliance with regulations, sharia principles, operational standards for sharia FinTech governance, and the Sharia Supervisory Board.Implication: With the existence of technology and the digital world, it will make easier life for human activities which can be accessed through any telecommunication media, anywhere, easy to use, and speeds up the process (Yudaruddin, 2022) . One of the outputs from the digital world is financial technology (FinTech). The development of FinTech can also be felt in Islamic finance where Islamic FinTech transactions in Indonesia in 2020 reached 2.9 billion in transaction volume and are the fifth largest transaction volume globally (Darmansyah et al., 2020; Muryanto, 2022; and Yudaruddin, 2022).Originality: This study looks directly at the FinTech phenomenon and compliance with sharia regulations in Islamic Banking in Indonesia which will be able to make good corporate governance of Indonesia Islamic Banking. Considering that there are not too many study at FinTech and sharia compliance in Indonesia Islamic Banks.